Pelatihan dan Pendampingan Maharah Kalam Santri dalam Pembelajaran Bahasa Arab di TKA/TPA - Nurazizah Amir; Nurjannah Nurjannah (Lembaga Penelitian dan Pengabdian Masyarakat UNWAHA, 2022)
Arabic is familiar to Muslims because the main source of teaching is the Qur'an and hadith, both of which use Arabic. In addition, the books of scholars in the field of Islamic sciences also use Arabic. Thus, Arabic is an urgent language to learn as Muslims. However, the Indonesian people, especially the millennial generation of students, still regard Arabic as a very difficult language to learn. Therefore, providing an understanding of the importance of learning Arabic needs to be done to the community so that they are able to recognize their identity as Muslims as a whole. Speaking skill (maharah kalam) is one of the most important aspects in learning Arabic because learning a foreign language will be easy if you are actively involved in communication efforts. Therefore, the author held training and mentoring activities for maharah kalam in learning basic Arabic at TKA/TPA Al-Ikhsan, Congkoe Hamlet, Lamatti Riaja Village, Bulupoddo District. The result of this activity is that in the process of learning Arabic, students show an enthusiastic attitude in receiving learning materials. This can be seen from their enthusiasm for learning, enthusiastic attitude in practicing vocabulary or conversation in front of friends, asking questions about the material that has been presented, and responding well to questions asked. Thus, the results of the learning evaluation show that students who have never studied Arabic are able to know well the lessons that have been taught and can pronounce Arabic vocabularies properly and correctly.